On the Optiml Variance of Money - Vincenzo Denicolò (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1989)
This paper analyses some monetary policy issues in a model of business cycle derived from Lucas (1972). We show that an autoregressive monetary policy rule may dominate a k-percent rule, and that the optimal monetary policy is characterised by an infinite amount of noise.
Keywords: 330